Sulfimine‐Promoted Fast O Transfer: One–step Synthesis of Sulfoximine from Sulfide. Issue 4 (8th February 2017) - Xie, Yongtao; Zhou, Biying; Zhou, Sha; Zhou, Shaa; Wei, Wei; Liu, Jingbo; Zhan, Yizhou; Cheng, Dandan; Chen, Minggui; Li, Yuxin; Wang, Baolei; Xue, Xiao‐song; et al.
Abstract: Transfer of electrophilic NH to sulfides and a subsequent sulfimine‐promoted fast O transfer have been achieved in a one‐pot process unprecedentedly for the preparation of sulfoximines at ambient temperature under air. The transformations, which are metal‐, ligand‐, base‐, additive‐free, and operationally simple, proceed in just 5 min and furnish NH ‐sulfoximines in good‐to‐excellent yields (up to 99 %) by treatment of sulfides with a combination of PhI(OAc)2 and ammonia source. A variety of commercially available and inexpensive electrophilic nitrogen sources are successfully used in the oxidative sulfide‐to‐sulfoximine conversions. This method features a high efficiency, excellent functional‐group tolerance, and broad substrate scope, which may facilitate its applications in medicinal chemistry area. Abstract : Synthesis of NH ‐sulfoximines from Sulfides by Transfer of Electrophilic NH and O Atom in a very Short Time at Ambient Temperature Under Air with no External Preactivation.